Approach to differential diagnosis of learning difficulties and mental retardation - Pérez Martinto, Pedro Carlos (2015)
The learning difficulties are a diagnostic entity. It is result of group of factors that determine the limitations that schoolchildren express in the learning process. It is necessary to understand that there are distinctive features to differentiate these difficulties (signs and symptoms) with other similar or more complex entities because of their inherent manifestations and causes. A set of components was given to the seventh cycled students of the Psychology Career in order to achieve an interdisciplinary support of different specialties in educational institutions where they grow professionally.